부착반: 구조, 관련 질병 및 신호역학 - 홍지윤; Jiyun Hong; 이기종; Ki-jong Rhee (Korean journal of clinical laboratory science, 2025)
부착반은 세포 간 접착을 담당하는 특수한 세포 연결 구조로, 기계적 스트레스 환경에서도 조직의 응집력과 구조적 안정성을 유지하는 데 중요한 역할을 한다. 부착반은 데스모글레인과 데스모콜린과 같은 막관통 캐드헤린과 플라코글로빈, 플라코필린, 데스모플라킨과 같은 세포질 단백질로 구성되며, 이들은 중간 필라멘트와 결합하여 강력한 접착 네트워크를 형성한다. 부착반은 단순히 세포 간 접착을 제공하는 것에 그치지 않고, 세포 신호전달, 조직 재구성, 생리적 조절 과정에 관여하여 조직이 기계적 스트레스에 적응하도록 돕는다. 부착반 단백질의 발현은 조직의 특수한 기계적 및 기능적 요구에 따라 조절되며, 중층 상피, 심장 조직, 단층 상피 등 다양한 조직에서 관찰된다. 부착반 구성요소의 이상은 자가면역 질환, 부정맥성 심근병증과 같은 심혈관 질환 및 암 등 여러 질환과 관련이 있으며, 접착 및 신호 전달 경로에 영향을 미친다. 본 논문에서는 부착반의 구조적 역할뿐만 아니라 조절 중심체로서의 기능에 대해 다양한 연구 결과를 종합하여 논의하며, 조직 구조 유지와 생물학적 과정 조율에서의 중요성을 강조한다. Desmosomes are a type of cell-to-cell junction, specialized intercellular structures that maintain tissue cohesion and structural integrity under mechanical stress. These complexes consist of transmembrane cadherins, including desmogleins and desmocollins, along with cytoplasmic proteins, such as plakoglobin, plakophilin, and desmoplakin, forming an adhesive network that links intermediate filaments. Beyond facilitating adhesion, desmosomes participate in cellular signaling, tissue remodeling, and physiological processes, allowing tissues to adapt to mechanical challenges while preserving organization. Desmosomes comprise transmembrane proteins that facilitate adhesion and cytoplasmic components that connect the adhesive interface to intermediate filaments to maintain structural organization. The expression of desmosomal proteins, including isotype and isoform variations, is adapted to the specific mechanical and functional needs of tissues, including stratified epithelia, cardiac tissue, and simple epithelia. Disruptions in desmosomal components are associated with various conditions, including autoimmune diseases, cardiac disorders such as arrhythmogenic cardiomyopathy, and cancers, where they influence adhesion and signaling pathways. This review reports numerous findings to provide a detailed understanding of desmosomes as structural connectors and regulatory hubs, emphasizing their importance in maintaining the tissue structure and coordinating biological processes across different systems.